2015
DOI: 10.17017/j.fish.98
|View full text |Cite
|
Sign up to set email alerts
|

Study on the Socio-Economic Condition of Fishermen of the Punorvaba River under Sadar Upazila, Dinajpur

Abstract: The present study was conducted to evaluate livelihood status of fishing community of the Punorvaba River under Dinajpur Sadar Upazila during the period from January to August, 2013. The livelihood status of fishermen were studied in terms of age structure, family size and type, occupation status, educational status, housing condition, drinking water facilities, sanitary facilities, health facilities, credit facilities and monthly income. It was found that most of the fishermen were belonged to the age groups … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 0 publications
1
8
0
Order By: Relevance
“…In general, there is a greater homogeneity of coastal fishing communities. The fishing families tend to live in a single village due to their low social status [ 23 ]. After selecting the villages mentioned above, a list of CSG participant women was collected from the ECOFISH team.…”
Section: Methodsmentioning
confidence: 99%
“…In general, there is a greater homogeneity of coastal fishing communities. The fishing families tend to live in a single village due to their low social status [ 23 ]. After selecting the villages mentioned above, a list of CSG participant women was collected from the ECOFISH team.…”
Section: Methodsmentioning
confidence: 99%
“…A study by Hossain et al, (2015) on the Punorvaba River in Dinajpur revealed some problems with fishing in the Punorvaba River like shortage of fishing boats, insufficient fishing gear, marketing of fish, Influence of the local political leaders and muscle men, regular flooding of the river, inadequate of credit facilities and use of destructive, and destructive and illegal fishing gears (F. I. Hossain et al, 2015).…”
Section: Review Of Literaturementioning
confidence: 99%
“…A study by Hossain et al, (2015) on the Punorvaba River in Dinajpur revealed some problems with fishing in the Punorvaba River like shortage of fishing boats, insufficient fishing gear, marketing of fish, Influence of the local political leaders and muscle men, regular flooding of the river, inadequate of credit facilities and use of destructive, and destructive and illegal fishing gears (F. I. Hossain et al, 2015). Afrad et al, (2019) conducted a study on the fish biodiversity and livelihood status of the fishermen living around the Titas River in Brahmanbaria district of Bangladesh and identified four major problems in the lives of the fishermen of the study area.…”
Section: Review Of Literaturementioning
confidence: 99%
See 1 more Smart Citation
“…it is also referred to as the systematic procedure of a livelihood based on abilities, resources, and feasibility. In an effort to resolve the issue of the sustainability of farmers' livelihoods, livelihood security and farmer quality in poor areas are regarded as major issues, as well as a vital research hotspot for specialists and researchers [2,20].…”
Section: Introduction 11 Background Of the Studymentioning
confidence: 99%